Perubahan Budaya dan Tinjauan Islam terhadap Manajemen Mutu Terpadu Pendidikan Islam di Pondok Pesantren Daar El Manshur - Ade Salamun; Maemunah Sa’diyah (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
This study aims to provide an overview of the process of cultural change through total quality management in Islamic perspective carried out at Daar El Manshur Islamic Boarding School. The method of the study is qualitative method by using in-depth interview techniques with informants. This research was conducted at the Daar El Manshur Islamic Boarding School, Depok City, West Java. Data analysis was carried out using content analysis with the stages of reducing data, triangulating data, presenting data descriptively, and drawing conclusions/verification. The results showed that cultural change through total quality management at Daar El Manshur Islamic Boarding School was seen from 7 focuses. The focus of planning for Islamic boarding schools is still focused on current conditions. The focus of the organization is participatory by involving all individuals to improve the quality of education and to develop Islamic boarding schools. The focus of control is still in the form of monitoring and supervising each section based on the existing SOP. The focus of communication has been two-way communication. The focus of the decision is still reactive and not based on well planning even though decisions are made based on deliberation and consensus. The focus of functional management has not been fully integrated. The focus of quality management is still reactive because it is still in the stage of finding the best and most suitable method to be applied in Islamic boarding schools. Therefore, the process of cultural change at Daar El Manshur Islamic Boarding School has begun to occur.